PENINGKATAN DAYA SAING PENDIDIKAN MELALUI MANAJEMEN MUTU ISO 9001 : 2008 - Faizin Faizin; Wardatus Sholehati (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2019)
Implementation of ISO 9001: 2008 quality management system will be a solution for educational institutions in dealing with problems and threats that can reduce the quality of educational institutions. Institutional marketing and student output generated through a good learning process will result in good academic and non-academic achievements. To realize a better quality educational institution, an institution should always evaluate the quality improvement program continuously, this system will become a strategic tool in increasing the institution's competitiveness in accordance with the demands of the times and the desires of customers, educational institutions as a form of service services are required to form good and capable human resources that are competitive in accordance with educational goals. Adopting the ISO quality management system and implementing its principles well will improve management within an institution so that its management is good and the performance of internal and external members can collaborate well to realize the goals of the institution in accordance with National Education Standards.